Impact of land use changes on the tsunami hazards in part of coastal Kebumen - Pamungkas, Bagus; Mardiatno, Djati; Retnowati, Arry (Universitas Gadjah Mada, 2023)
This research was conducted to analyze land use change from 2016 to 2022 and their impact on the tsunami hazard zone on the coast of Kebumen Regency. For land use change analysis, remote sensing, geographic information systems (GIS), and statistical tests were applied to Sentinel-2A satellite imagery. The tsunami hazard was simulated using tsunami inundation modeling based on land use spatial data and DEMNAS processed using GIS. Land use changes occurred significantly in the study area, especially in Mirit District. The Southern Cross Road (JJLS) and coastal morphological conditions influence land use change patterns. Land use changes impact changes in the tsunami hazard zone, especially in the use of fir forests and shrimp ponds. The research findings can be used as input for developing a tsunami disaster mitigation plan and detailed spatial planning on the coast of Kebumen Regency.